Synovial biopsies in inflammatory arthritis: precision medicine in rheumatoid arthritis. (3rd March 2020) - Small, Annabelle; Wechalekar, Mihir D
ABSTRACT: Introduction : Synovial tissue (ST) is composed of a lining and sublining layer and is the target tissue involved in the inflammatory arthritides (IA), in which there is lining layer hyperplasia, inflammatory cell influx, macrophage recruitment and change in number and behavior of lining fibroblasts. Understanding synovial pathology has been critical in providing insights into pathogenetic mechanisms of disease and therapeutics. Pathobiological insights into ST have been underpinned by progress in molecular analytic methods; research in this area holds promise in individualizing treatment and optimizing response. Areas covered : We explore ST in IA and cover in-depth the utility of synovial biopsy and ST heterogeneity. We review recent advances in ST research and discuss implications with regards to therapeutic response. Finally, we provide perspectives on the identification of new drug targets and new diagnostic and prognostic markers. Expert opinion : ST holds the potential to individualize therapy by detecting biomarkers of diagnosis, therapeutic choice, and treatment modification in IA. Advances in molecular biology including high-throughput omics are likely to provide information that has hitherto remained unknown. ST analyzes pre- and post-treatment needs to be standard of care; only by routinely collecting and analyzing ST will we achieve the precision medicine outcomes described herein.